Effectiveness of Large-Scale Social Restrictions (PSBB) toward the New Normal Era during COVID-19 Outbreak: a Mini Policy Review - Andriani, Helen (UI Scholars Hub, 2020)
The government of Indonesia has not used lockdown or quarantine as an option to tackle the spread of Coronavirus, as the impact of lockdown on small communities in the informal sector that lives from daily income will be severe. Alternatively, the government is enforcing Large-Scale Social Restrictions (Pembatasan Sosial Berskala Besar or